The pseudorabies virus UL28 protein enters the nucleus after coexpression with the herpes simplex virus UL15 protein - Koslowski, Kim M.; Shaver, Patti R.; Wang, Xiao-Yang; Tenney, Daniel J.; Pederson, Nels E. (East Carolina University, 1997)
Herpesvirus DNA is packaged into capsids in the nuclei of infected cells in a process requiring at least six viral proteins. Of the proteins required for encapsidation of viral DNA, UL15 and UL28 are the most conserved among herpes simplex virus type 1 (HSV), varicella-zoster virus, and equine herpesvirus 1. The subcellular distribution of the pseudorabies virus (PRV) UL28 protein was examined by in situ immunofluorescence. UL28 was present in the nuclei of infected cells; however, UL28 was limited to the cytoplasm in the absence of other viral proteins. When cells expressing variant forms of UL28 were infected with a PRV UL28-null mutant, UL28 entered the nucleus, provided the carboxyl-terminal 155 amino acids were present. Additionally, PRV UL28 entered the nucleus in cells infected with HSV. Two HSV packaging proteins were tested for the ability to affect the subcellular distribution of UL28. Coexpression of HSV UL15 enabled PRV UL28 to enter the nucleus in a manner that required the carboxyl-terminal 155 amino acids of UL28. Coexpression of HSV UL25 did not affect the distribution of UL28. We propose that an interaction between UL15 and UL28 facilitates the transport of a UL15-UL28 complex to the infected-cell nucleus. Originally published Journal of Virology 1997 Vol. 71, No. 12.
Keywords: Herpes virus; Viral Proteins; Viral DNA; Pseudorabies virus